An appraisal of rain shadow effects and livelihood dynamics in the Attappady hilly region, Western Ghats, Kerala - Suresh P (Government College Chittur, Palakkad, 2025)
Human life is closely linked to the climate of its surroundings. Climatic factors are often governed by the topographic features. Attappady hilly regions of Palakkad district is located in the eastern part of Western Ghats, experiencing the decreasing rainfall from west to east due to the rain shadow effect. Rain shadow refers to a climatic phenomenon where one side of a mountain range receives significantly more precipitation than the other, leading to a dry area on the leeward side. Unlike the humid western slopes, eastern Attappady receives drastically lower rainfall and leads to significant microclimatic variation, land degradation and livelihood vulnerability. This research investigates genesis and process of the rain shadow phenomenon, its spatial extent, and role of the climatic and topographic factors in the developing of rain shadow in Attappady hilly region. This study investigates the impacts of rain shadow effects on agriculture practice, land degradation, soil quality, and livelihood dynamics of the people of Attappady hilly region. The methodology applied in the study are Geospatial techniques (GIS, Remote sensing, AHP, and MIF), Statistical Analysis (SPSS, PCA, Correlation and Regression), and Field surveys. Major findings of the study revealed that eastern Attappady experiencing more rain shadow effects and approximately 60% of Attappady lies in the rain shadow zone. These areas face severe rainfall scarcity, increasing temperature, and low agriculture productivity due to the rain shadow effects. Soil quality analysis showed that 20% of the regions have poor Soil Quality Index, aligning with zones of high degradation. Livelihoods of people have shifted from agriculture to wage labour, and 84.9% of respondents associating climate changes with the rain shadow effect. To address the rain shadow effects and its associated issues, researcher recommends a sustainable development model for achieve durable improvements in agriculture and land productivity, water conservation, and livelihood security through the people participation in the Attappady hilly region of Palakkad district.
Keywords: Rain Shadow Effect; Land Degradation; Soil Quality Index; Sustainable Agriculture and Geospatial Technology.